Somatic Mutations and Autoimmunity - Maha Alriyami (Cells, 2021)
Autoimmune diseases are among the most common chronic illness caused by a dysregulated immune response against self-antigens. Close to 5% of the general population in Western countries develops some form of autoimmunity, yet its underlying causes, although intensively studied, are still not fully known, and no curative therapies exist. It is well established that autoimmune diseases have common mechanisms and are caused by both genetic and non-genetic risk factors. One novel risk factor that can contribute to autoimmunity is somatic mutations, in a role parallel to their role in cancer. Somatic mutations are stochastic, de novo, non-inherited mutations. In this hypothesis, the persistent proliferation of self-reactive lymphocytes (that is usually hindered by a series of checkpoints) is permitted, due to somatic mutations in these expanding cells, allowing them to bypass multiple regulatory checkpoints, causing autoimmunity. This novel concept of the contribution of these mutations in non-malignant diseases has recently started to be explored. It proposes a novel paradigm for autoimmunity etiology and could be the missing piece of the autoimmunity puzzle.